Why do people pay zakah, infaq, and sadaqah (ZIS) through donation-based crowdfunding? The influence of Technology Acceptance Model and Social Presence Theory - Aulia, Defrina; Pimada, Laila Masruro (Journal of Islamic Economics Lariba, 2023)
IntroductionIndonesia has the largest Muslim population in the world and a large potential for zakat, infaq, and sadaqah (ZIS). However, in reality, ZIS revenue is only 5% of its potential. Crowdfunding was built to encourage the acceptance of ZIS to reach its potential by using only gadgets connected to the Internet. However, not all individuals are willing to use crowdfunding because of their individual considerations and preferences.ObjectivesThis study aims to identify the decision preferences of muzakki and donors to pay zakat, infaq, and alms using a crowdfunding platform. MethodThis study uses quantitative methods with PLS-SEM analysis tools with preference measurements using the Technology Acceptance Model and social presence theory framework.ResultsThe results of this study indicate that perceived usefulness, perceived ease of use, social presence, and trust have a significant positive effect on the preference decision to pay ZIS with crowdfunding. The trust variable also significantly mediates the relationship between social presence and the decision to pay ZIS through crowdfunding. ImplicationsThis research is expected to be a consideration for zakat management organizations (OPZ) for the development of a better platform to encourage community participation in channel funds to pay ZIS.Originality/NoveltyThis study is unique in its approach to crowdfunding in Indonesia’s ZIS context. It contributes to the body of knowledge on the maximization of ZIS potential in Muslim societies.